2017
DOI: 10.1080/08109028.2017.1408289
|View full text |Cite
|
Sign up to set email alerts
|

Managing the transition to open access publishing: a psychological perspective

Abstract: To manage the transition to the open access (OA) model of scholarly publishing, we need to understand better what enables, encourages and inhibits the adoption of OA publishing among scientists, and to appreciate individual differences within disciplines. The study adopts a psychological perspective to elucidate motivations, capabilities and opportunities for OA publishing among bioscientists in the UK. To identify differences within the discipline, bioscientists with starkly different past practices for discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…10 A third study also explored biomedical publishing and found that, instead of discipline, a major source of differences in OA uptake was the authors' "past knowledge-disclosure practices," such as in commercial patents versus open-source software. 11 Our study hoped to clarify both the prevalence of the various motives for OA authors and the extent of disciplinary differences.…”
Section: Literature Reviewmentioning
confidence: 98%
“…10 A third study also explored biomedical publishing and found that, instead of discipline, a major source of differences in OA uptake was the authors' "past knowledge-disclosure practices," such as in commercial patents versus open-source software. 11 Our study hoped to clarify both the prevalence of the various motives for OA authors and the extent of disciplinary differences.…”
Section: Literature Reviewmentioning
confidence: 98%
“…The cost of publication also triggered authors' concerns about how to pay, which impacted their submission decision (Schroter & Tite, 2006). Weckowska et al (2017) also found that authors considered whether the publishing cost was proportional to the publication gain.…”
Section: Resultsmentioning
confidence: 99%
“…Timeliness was measured by the overall time from submission to publication or specific sub‐processes. Several surveys found that shorter turnaround time was a motivating factor to select OA journals (Jamali et al, 2020; Weckowska et al, 2017). The time for three key sub‐processes (i.e., review, response, and publication) also affected journal selection.…”
Section: Resultsmentioning
confidence: 99%
“…The research fronts are inspired and raised from the common intellectual base. Through the function of cluster exploration of CiteSpace, the research fronts could be drawn, including predatory publishing (Perlin et al, 2018), academic publishing (Lillis et al, 2010), global sociology (Sorokin, 2018), behavioral disorders (Cook, 2016), whipping boys (Hess & Hoerndlein, 2015;Kingsley & Kennan, 2015a, 2015b, academic librarians (Baro & Eze, 2017;Bosah et al, 2017), linguistic injustice (Hyland, 2016), and open access publishing (Weckowska et al, 2017;Zhu, 2017). Timeline visualization in CiteSpace depicts clusters along horizontal timelines (C. Chen, 2017, p. 15).…”
Section: Reference Co-citationmentioning
confidence: 99%